The effect of fentanyl on Clinical Symptoms and Hemato- Biochemical Parameters in Dogs (Journal of Hama University, 2020)
The Present study was designed to evaluate the  effect  of  fentanyl on some blood parameters and note some vital reflexes(Heart rate ,analgesia, absence of sensory reflexes ,respiratory rate and temperature degree)which are shown by dogs during injection and after injection. For this purpose ,six dogs with no breed of about  7-9 kg body weight and Aged between 3-4 years where blood samples were taken before injection  then injected intravenously with fentanyl after that  blood samples were taken after 15,30,60,120 minutes and after 24 hour. Then sensory reflexes are  recorded according  to previous intervals. As a result , heart rate ,respiratory rate showed significant decrease (P